Uso do transporte coletivo do município de São Carlos (SP) por parte da comunidade universitária da Universidade Federal de São Carlos (UFSCar) - Trindade, João Vítor Araujo (2019)
In the present work an analysis of the issue of urban mobility by public transportation, focusing on the students of the Federal University of São Carlos, in the city of São Carlos (SP), is carried out. Concepts related to collective transportation and sustainable urban mobility are presented, as well as a theoretical basis on the use of collective transportation by university students and surveys and public transport research. The execution of these surveys through a questionnaire will be essential for the determination of a travel pattern for this group, both in statistical and spatial aspects, with the help of online forms, Geographic Information Systems softwares, and spreadsheets. Due to a better contextualization of the work, a characterization of the municipality of São Carlos in relation to its urban and population evolution and its public urban transport system is carried out. As main results, it was found that collective transportation is the most used mode, followed by automobiles and walking, the latter being more frequently used by those who live near the university. Travel origins are concentrated in some specific neighborhoods of the municipality, which have a good level of access to services and public transportation, or are close to the campus. The users of public transportation to the university (35% of respondents) are, for the most part, undergraduate students, aged between 18 and 23 years and monthly income up to R$1,999.